Chelator Probe with Exceptionally High Stokes Shift for Selective Detection of OAc− with Red Emission: Application as a Biosensor. Issue 4 (29th January 2018) - Pramanik, Koushik; Ghosh, Pritam; Dey, Debanjan; Malpaharia, Pijush; Chandra, Swapan K; Mukhopadhyay, Subhra Kanti; Banerjee, Priyabrata
Abstract: A novel chelator probe with flexible structural configuration has been synthesized as chemosensor for selective detection of biotic anion like OAc − by chromogenic as well as fluorogenic signal. The nitro substituted chelator probe has shown pale yellow to deep yellow coloration upon detection of OAc − ion. Significantly the emission of the chelator probe upon recognition of the anion has been turned ON in low energy region which has been explained through PET‐ESIPT‐ILCT‐C=N isomerisation based pathways. The chelator probe has shown exceptionally high stroke's shift. The host guest interaction has been confirmed by different sophisticated analytical tools such as UV‐Vis, fluorescence, 1 H‐NMR and FT‐IR. Significantly the fluorescence turn on phenomena has been utilized to detect intracellular OAc − inside candida albicans to explore the applicability of the chelator probe as bio sensor. Abstract : Imine based Schiff base chemosensor has been synthesized by condensation reaction for selective detection of OAc − like biotic anions by fluorescence turn on and chromogenic phenomena. The probe with flexible geometry has exceptionally high stokes shift. DFT has been performed to investigate the energy difference between frontier molecular orbitals. The detection of biotic ions has been executed inside Candida Albicans .